Quo Vadis UU Ormas dalam Dinamika Gerakan Islam Indonesia - Agus Irfan (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
This article discusses the ‘Quo Vadis Act’ on Mass Organizations law No 2, 2017 throughout the dynamics of the Islamic movement in Indonesia which will be described in two sub-formulation of the problems: 1. What are the motive and purpose of the birth of the Ordinance Act? 2. How does the response of the Islamic groups movement in Indonesia in seeing the mass organizations law? Furthermore, the results show that in order to protect the sovereignty of the Unitary Republic of Indonesia from radical ideas that contradict Pancasila as the ideology and philosophy of ‘NKRI’, the government has issued the Ordinance Act. Moreover, various responses appear; the anti-mainstream Islamic movement group represented by Hizb Tahrir Indonesia (HTI) has rejected the birth of the mass organization law. Although the reason for the birth of the law is considered as violating the freedom of human rights, however, the rejection is actually more to the historical-ideological reason. They consider that as an ideology of the country, Pancasila does not represent the teachings of Islam that requires the formalization of sharia. Meanwhile, for the mainstream Islamic group represented by Nahdlatul Ulama (NU), the ideology issued is an ijtihâdî region which focuses on the welfare and implemented on the basis of mutual commitment (al-Muslimūn bisyurūthihim). With that benefit approach, hence the birth of this social organizations act is judged appropriate at least as a preventive and a protective measures which have been undertaken by the government to maintain the integrity of NKRI and Pancasila as the ideology of the country.